Renal Inflammation and Innate Immune Activation Underlie the Transition From Gentamicin-Induced Acute Kidney Injury to Renal Fibrosis - Albino, Amanda Helen; Zambom, Fernanda Florencia Fregnan; Foresto-Neto, Orestes; Oliveira, Karin Carneiro; Ávila, Victor Ferreira; Arias, Simone Costa Alarcon; Seguro, Antonio Carlos; Malheiros, Denise Maria Avancini Costa; Camara, Niels Olsen Saraiva; Fujihara, Clarice Kazue; Zatz, Roberto (Frontiers in Physiology, 2021)
Subjects recovering from Acute Kidney Injury (AKI) are at risk of developing Chronic Kidney Disease (CKD). The mechanisms underlying this transition are unclear and may involve sustained activation of renal innate immunity, with resulting renal inflammation and fibrosis. We investigated whether the NF-kappa B system and/or the NLRP3 inflammasome pathway remain activated after the resolution of AKI induced by gentamicin (GT) treatment, thus favoring the development of CKD. Male Munich-Wistar rats received daily subcutaneous injections of GT, 80 mg/kg, for 9 days. Control rats received vehicle only (C). Rats were studied at 1, 30 and 180 days after GT treatment was ceased. On Day 1, glomerular ischemia, tubular necrosis, albuminuria, creatinine retention and tubular dysfunction were noted, in association with prominent renal infiltration by macrophages and myofibroblasts, along with activation of the NF-kappa B and NLRP3 innate immunity pathways. Regression of functional and structural changes occurred on Day 30, but local RAS and the NF-kappaB system remained activated, and interstitial fibrosis was evident. On Day180, recurring albuminuria and mild glomerulosclerosis were seen along with glomerular ischemia and unabated interstitial fibrosis, whereas macrophage infiltration was still evident. GT-induced AKI activates innate immunity and promotes renal inflammation. Persistence of these abnormalities provides a plausible explanation for the transition of AKI to CKD observed in a growing number of patients.